Zyxin as a potential cancer prognostic marker promotes the proliferation and metastasis of colorectal cancer cells. Issue 9 (29th January 2019) - Zhong, Chenhan; Yu, Jiekai; Li, Dan; Jiang, Kai; Tang, Yang; Yang, Mengyuan; Shen, Hong; Fang, Xuefeng; Ding, Kefeng; Zheng, Shu; Yuan, Ying
Abstract: Colorectal cancer (CRC) is a leading cause of cancer death. This study was conducted to investigate the functions and mechanisms of Zyxin (ZYX) in CRC. Multiomics analysis associated ZYX with CRC metastasis. ZYX expression levels were increased in human CRC tissues and related to shorter recurrence‐free survival. Knockdown of ZYX expression resulted in inhibition of cell growth, invasion, and migration in vitro and in vivo. Comprehensive analysis of gene microarray analysis showed that ZYX may activate the pathway of NUPR1 and JNK, inhibit CST5, regulate focal adhesion (FA), and affect epithelial–mesenchymal transition in CRC cells. Results of gene microarray and membrane protein isobaric tags with relative and absolute quantitation labeling mass spectrometry found ten differentially expressed genes, which were associated with ZYX activity. Furthermore, real‐time polymerase chain reaction was used to validate the expression patterns of selected genes in the integrative analysis. Taken together, our findings provide the first evidence that decreased expression level of ZYX impairs CRC cell proliferation and metastasis probably via the FA pathway. Abstract : In our study, we investigated the involvement of Zyxin (ZYX) in colorectal cancer, demonstrating its role in enhancing tumor cell proliferation and metastasis. Gene ontology, Kyoto Encyclopedia of Genes and Genomes, and STRING analyses of the this data showed that cell adhesion‐related genes and the focal adhesion pathway were greatly affected after ZYX silencing. The gene microarray and proteomic analyses opened the opportunity to investigate and possibly define the molecular effects of ZYX silencing.